The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1361-6463/ab8e30
|View full text |Cite
|
Sign up to set email alerts
|

Isotope tracing experimental study on the effects of trace H2O on the over-thermal decomposition of SF6

Abstract: It has been recognized that the gas insulating medium SF6 decomposes when the partial over-thermal fault (POF) occurs inside the equipment. The insulation condition monitoring and fault diagnosis of the equipment can be carried out by utilizing the decomposition characteristics of SF6 under POF. Similar to the discharge decomposition of SF6, trace H2O is an important factor affecting the decomposition of SF6 under POF while its mechanism is not clear yet. In order to investigate the characteristics and micro m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In addition, in order to clarify the influence of O 2 or H 2 O on the discharge decomposition characteristics of the gas insulating medium, a non-radioactive isotope tracer method can be considered to reveal the method of decomposition and by-product generation by detecting the residual isotope content or isotope consumption after discharge and the isotope distribution in characteristic decomposition products [43].…”
Section: Discharge Decompositionmentioning
confidence: 99%
“…In addition, in order to clarify the influence of O 2 or H 2 O on the discharge decomposition characteristics of the gas insulating medium, a non-radioactive isotope tracer method can be considered to reveal the method of decomposition and by-product generation by detecting the residual isotope content or isotope consumption after discharge and the isotope distribution in characteristic decomposition products [43].…”
Section: Discharge Decompositionmentioning
confidence: 99%
“…[5]. On the one hand, some decomposition products are corrosive, which may cause certain damages to the equipment [6,7]. On the other hand, the stability and insulation of the decomposition gases are far inferior than that of SF 6 [8].…”
Section: Introductionmentioning
confidence: 99%
“…With reference to the studies of Van Brunt and Zhao, Zeng et al used the isotope tracing method to study the decomposition of SF 6 under partial over‐thermal fault. The influence mechanism of H 2 O on the formation of main products was investigated [51]. They concluded that the generation of CO 2 is not sensitive to the content of H 2 O while SO 2 , SO 2 F 2 and SOF 4 are very sensitive to H 2 O content.…”
Section: Progress In Sf6 Decomposition Characteristics and Mechanismmentioning
confidence: 99%